Windows and mirrors : representing the self and another in the personal essay : a thesis presented in partial fulfilment of the requirements for the degree of Master of Creative Writing at Massey University, Distance, New Zealand - Brown, Jessica Rachael (Massey University, 2022)
This Master of Creative Writing research project consists of two parts: a critical essay exploring how authors of the personal essay weave together their voice with the voices of others, and my own collection of personal essays exploring how to do the same. The critical essay examines personal essays by Alexander Chee, Valeria Luiselli and Leslie Jamison. In each of these essays, the author draws attention to an issue of wider significance by weaving together their own stories with the stories of one or numerous others. I have chosen these three authors and essays because they demonstrate the varied narrative positions an author of personal essays can use in writing other’s stories and stories about broader public issues. For example, Chee is alongside the AIDS epidemic but not a victim in the traditional sense of living with and dying from AIDS. Luiselli is both within and alongside the migration crisis as she is a Mexican woman going through the immigration process even if she did not ride La Bestia to get to America, like most of her interviewees did. While Jamison is a patient herself using her story to represent the story of others. The shift in perspective of the three essays, ranging from Chee’s alongside the issue to Jamieson’s inside, shows possibilities for how an author might highlight an issue of wider significance regardless of their position in relation to the issue, witness, insider or somewhere in between. I argue that weaving together personal stories with the stories of others allows broader issues to emerge as the story transcends the individuals involved. Each author uses different techniques to achieve this, showing the scope of possibilities that I could adapt to my own collection. The creative component of my thesis is a collection of personal essays. My essays have their roots in the everyday experiences of life. By writing these essays, I have tried to make sense of what it means to be human. For example, what does it mean to be a daughter? What does death look like when it shows up unexpectedly? And when it is long waited for? How can I describe the symbiosis between my body, heart and mind? How can I describe dreams or luck or loss? How can I make visible the hidden choices that make up all of our lives, the compromises we make jutted up against the small victories. My essays describe the human experience as seen through my eyes. In some essays, my eyes gaze upon the experience of others and witness their moments of struggle and growth within the minutia of everyday life. I have sought to capture their voice in these moments while also sharing how their experiences have impacted and changed me. Some of the experiences are universal and can be recognised by others as they read, and some experiences will be novel and specific to me or those I write about. As the authors explored in the critical essay presented many different techniques for weaving their story together with that of another, I have experimented with those possibilities. The resulting collection includes a range of subjects in various formats, including one instance of autobiographical fiction.
Keywords: 360201 Creative writing (incl. scriptwriting)